GERAKAN SYARIKAT ISLAM KEMBALI KE KHITTAH TAHUN 1905 - Wardiono, Gugun -; Sugiarto, Bowo; Rofik, Ahmad (JPP (Jurnal Politik Profetik), 2020)
The article aims to describe the causes of Syarikat Islam which returned to khittah 1905 (original path) and the process of this organisation to return to it. This study conveys the factors which are influenced Syarikat Islam to decide to turn back to its original path: 1. The fragmentation of political Islam and the low level of competitiveness of Islamic party in legislative elections after the New Order era; 2) Internal conflict within Syarikat Islam has caused this organization fragmented and inactive for years. The idea to return to its original path is considered as a solution to reunite previously-fragmented factions within the organization. To realize that agenda, Syarikat Islam has utilized mobilizing structures that includes organizational consolidation and its members’ social networks.